Diversity and utilization of indigenous wild edible plants and their contribution to food security in Turkana County, Kenya - Oduor, Francis Odhiambo; Kaindi, Dasel Wambua Mulwa; Abong, George Ooko; Thuita, Faith; Termote, Céline (Frontiers Media, 2023)
Introduction Indigenous Wild edible plants (IWEPs) are consumed daily in some form by at least one in seven people worldwide. Many of them are rich in essential nutrients with the potential for dietary and nutrition improvement particularly for poor households. They are, however, often overlooked. This study investigated diversity, consumption frequency, and perceptions of IWEPs and the contribution they make to the food security of communities in Turkana County, northern Kenya. Our findings are aimed at stimulating targeted discussions among stakeholders involved in food security programs on best way to overcome the poverty stigma associated with IWEPs consumption and to promote their utilization for food security, nutritional and dietary improvement, and enhanced community resilience. Methods Applying a mixed-methods approach, we collected data using 12 gender-disaggregated focus group discussions and a questionnaire applied to a random sample of 360 households. Results and Discussion Participants identified 73 IWEPs, of which 24 were consumed in the preceding six months by 48.5% of households. Almost all surveyed households (96%) were classified as severely food insecure, and food insecurity did not differ significantly between households that consumed IWEPs and those that did not. Our results indicate that more IWEPs consumers than non-consumers reported eating foods they had not wanted to consume to cope with food scarcity, as well as having to eat fewer meals than normal. Just over half of the respondents (57.1%) held positive attitudes towards IWEPs, which was positively associated with a higher likelihood of IWEPs consumption. Long distances to harvest sites, lack of knowledge about the plants, their seasonality, and how to cook them appetizingly, coupled with overall unfavorable perceptions, are probable reasons for non-consumption of IWEPs among the survey respondents. In line with other studies cited on wild foods, we conclude that IWEPs have the potential to bridge food and nutritional deficits in food insecure households in the study area, although currently their consumption remains limited. Given this potential, further analysis of IWEPs’ nutritional composition and restoration of wild edible foods to local areas should be given priority, as well as interventions that help to overcome the challenges to their consumption and promote their wider use.